(untitled) (Journal of Pharmaceutical Negative Results, 2023)
There are various mosquitos borne diseases playing major role of transmission as vector; these include dengue, malaria, filariasis and yellow fever. Various places around us everywhere act as breeding sites for different developmental stages of mosquitoes. Variety of chemicals are being used to control breeding and spread of mosquitoes which include mercuric chloride, phenols, Paris green cresols, naphthalene, Bordeaux mixture, calcium arsenate, rosin-fish oil soap, and nicotine sulfate which are prone to various risks on environment and biodiversity. In present study an alternative approach of control through insectivore fish Poecilia reticulata and Poecilia sphenops was used against mosquitoe’s larvae as an alternative approach. The predation effect of insectivore fish on mosquito larvae (200) of culex and aedes was observed at different temperatures including 20oC, 25oC and 30oC for one hour duration and observation was recorded at 5 minutes interval. At 20oC the maximum consumption of larvae was observed at 35 minutes while for 25oC the maximum consumption was observed at 55 minutes similar results are observed at 30oC with increase of time for Poecilia reticulate. Poecilia sphenops also showed significant results at recorded temperatures. Also the morphometric parameters of mosquito’s larvae are shown in results which gave significant results. This study gave a useful alternate for control of breeding sites of mosquitoes which can save mankind from various serious mosquitoes’ related diseases.